Effect of miR-183-5p on Cholestatic Liver Fibrosis by Regulating Fork Head Box Protein O1 Expression - Wang, Yongxin; Chen, Bin; Xiao, Chengcheng; Yu, Jiang; Bu, Xiangyang; Jiang, Fengxing; Ding, Weijie; Ge, Zhong (Frontiers in Physiology, 2021)
Liver fibrosis is a common pathological feature of end-stage liver disease and has no effective treatment. MicroRNAs (miRNAs) have been found to modulate gene expression in liver disease. But, the potential role of miRNA in hepatic fibrosis s still unclear. The objective of this research was to study the potential mechanism and biological function of miR-183-5p in liver fibrosis. In this study, we used high-throughput sequencing to find that miR-183-5p is up-regulated in human fibrotic liver tissues. In addition, miR-183-5p was up-regulated both in rat liver fibrosis tissue induced by bile-duct ligation (BDL) and activated LX-2 cells according to the result of Quantitative real-time PCR(RT-qPCR). Moreover, the inhibition of miR-183-5p alleviated liver fibrosis, decreased the fibrotic biomarker levels in vitro and vivo and leads to LX-2 cells proliferation inhibition and apoptosis induction. The result of dual-luciferase assay revealed that miR-183-5p suppressed forkhead box protein O1 (FOXO1) expression by binding to its 3′UTR directly. Next，we used lentivirus to overexpress FOXO1 in LX-2 cells, we found that overexpression of FOXO1 reversed the promotion of miR-183-5p on liver fibrosis, including reduced the fibrotic biomarker levels in LX-2 cells, inhibited LX-2 cells proliferation and promoted apoptosis. Furthermore, overexpression of FOXO1 prevented the activation of the transforming growth factor (TGF)-β signaling pathway in TGF-β1-induced LX-2 cells according to the result of western blotting. In conclusion, the findings showed that miR-183-5p acted as a key regulator of cholestatic liver fibrosis, miR-183-5p promotes cholestatic liver fibrosis by inhibiting FOXO1 expression through the TGF-β signaling pathway. Thus, inhibition of miR-183-5p may be a new way to prevent and improve liver fibrosis.